Bridging the Emotional Divide in Instructional Design: A Kansei Perspective. - Chen, Chwen Jen; Chuah, Kee Man; Chee, Siong Teh (Springer Science+Business Media B.V., 2010)
Emotion has long been regarded as an obstacle to cognitive processes in learning. Despite various studies that showed strong influences of emotional state in learning, instructional designers tend to overlook its role when designing and developing instructional materials. This is mainly due to the lack of proper method or framework in linking emotions and instructions. Thus, with recent renewed interest on affective issues in instructions, this paper offers a fresh perspective by integrating Kansei Engineering methodology in the instructional design process. Kansei Engineering is a proven methodology for translating human feelings into a design. This paper describes how Kansei Engineering methods can be used to elicit important design elements of instructional materials that would in turn induce positive emotions on the learners and optimize effective learning.